Effect of Self-Efficacy and Technostress on Teacher Performance through Organizational Commitments - Magistra, Shaliha Nur; Santosa, Sigit; Indriayu, Mintasih (Fakultas Ekonomi, Universitas Negeri Semarang, 2021)
This study aimed to determine the effect of self-efficacy on the performance of high school teachers and organizational commitment, determine the effect of technostress on the performance of high school teachers, determine the effect of technostress on high school teacher and organizational commitment, and to know the effect of self-efficacy and technostress on the performance of high school teachers in Purwokerto through organizational commitment. The population in this study were 400 high school teachers in Purwokerto. The sample used a proportional random sampling. A questionnaire was used as a method of data collection. The data analysis method used a search method based on the SEM-path analysis model. The results showed that self-efficacy had a significant effect on the performance of high school teachers. Self-efficacy had a significant effect on the organizational commitment of high school teachers. Technostress had a significant effect on the performance of high school teachers. Technostress had a significant effect on the organizational commitment of high school teachers. Self-efficacy and Technostress had a significant effect on the performance of high school teachers in Purwokerto through organizational commitment.